BEL SEKOLAH TERPROGRAM BERBASIS MIKROKONTROLER ATMega32 - , ALEXANDER DAVID SIHOTANG; , Hidayat Nur Isnianto, ST.M.Eng ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Development of technology advances is very important these day as time passes almost all of the manual are converted into automation. Computerized system makes the user easier in solving all the problems. In the course of studying the school caretaker / teacher picket busy with activity when the school bell school hours, changing hours of admission, change of hours of study, rest, and home schools may be every day more than fivetimes . School bell is a device that can not be separated from the school . School bell lesson serves to give any sign of daylight saving time change to daylight saving time change. But unfortunately officers often forgotten in school bell at the right time, so that the lessons turn into chaos.